Escogidas plantas nuns and beatas in M exico City, 1531-1601 - Holler, Jacqueline Zuzann, 1964-; American Council of Learned Societies (New York, N.Y. : Columbia University Press, 2008)
Studies the origins of feminine religiosity in the early history of Mexico.
Caption title; description based on screen of 2008-03-30.
Originally published by Gutenberg-e: www.gutenberg-e.org.
Originally presented as author's thesis (Ph. D.)--Emory University, 1998.
Includes bibliographical references.
Electronic text (HTML) and image data (JPG).
This volume is made possible by a grant from the Andrew W. Mellon Fo undation.
Keywords: Monasticism and religious orders for women -- Mexico -- Mexico City; Convents -- Mexico -- Mexico City -- History; Women in Christianity; Women -- Religious life -- Mexico -- Mexico City; Mexico City (Mexico) -- Religious life and customs; Mexico City (Mexico) -- Social life and customs; Mexico City (Mexico) -- History -- 16th century; Mexico City (Mexico) -- Church history